Proceedings of the Second International Summit on Medical Nutrition Education and Research. (November 2016) - Barnes, K.; Crowley, J.; Laur, C.; Ball, L.; Ray, S.
Highlights: Key nutrition messages to be included in the medical curricula are needed. Medical professionals need to be able to differentiate between nutrition noise and science . Medical students are not expected to be nutrition experts but need to know how and when to refer. Engaging and innovative approaches are required for delivery of nutrition education in health care. Demonstrating the effectiveness of doctors is arguably the most important research priority.